Lending to Private Firms: Evidence from China on the Role of Firm Openness and Bribery. Issue 1 (2nd January 2018) - Ruan, Wenjuan; Xiang, Erwei; Ma, Shiguang
Abstract : This article investigates the effects of firm openness and bribery on bank lending decisions. Using World Bank data covering 1, 781 private firms, we do not find supportive evidence on the role of bribery in helping private firms to obtain bank credit. However, we find evidence that firm openness has a positive effect on helping private firms to obtain banking finance. This finding holds true only for large firms, manufacturing firms, and firms located in regions with good banking development. We also find that private firms with greater government assistance are more likely to obtain bank loans, and more credit overall.